Let $C_1 \lor \cdots \lor C_m$ be a 3CNF. We replace the clause $C_i = \ell_1 \lor \ell_2 \lor \ell_3$ with the clause $C'_i = \ell_1^{(i)} \lor \ell_2^{(i)} \lor \ell_3^{(i)}$, that is, with a clause which contains three literals, appearing only in that clause. For every variable $x_i$ and for every two clauses $C_j,C_k$ it appears in, we add a gadget that encodes, in a way, "$x_i^{(j)} = x_i^{(k)}$":
$$
\bar{x}_i^{(j)} \lor z_1^{(i,j,k)} \lor w_1^{(i,j,k)} \\
\bar{z}_1^{(i,j,k)} \lor z_2^{(i,j,k)} \lor w_2^{(i,j,k)} \\
\bar{z}_2^{(i,j,k)} \lor z_3^{(i,j,k)} \lor w_3^{(i,j,k)} \\
\bar{z}_3^{(i,j,k)} \lor x_i^{(k)} \lor w_4^{(i,j,k)} \\
\bar{x}_i^{(k)} \lor z_4^{(i,j,k)} \lor w_5^{(i,j,k)} \\
\bar{z}_4^{(i,j,k)} \lor z_5^{(i,j,k)} \lor w_6^{(i,j,k)} \\
\bar{z}_5^{(i,j,k)} \lor z_6^{(i,j,k)} \lor w_7^{(i,j,k)} \\
\bar{z}_6^{(i,j,k)} \lor x_i^{(j)} \lor w_8^{(i,j,k)}
$$
The resulting 3CNF is complete, as we show below. If we assign zero to all $w$ variables, then we get a 3CNF which is logically equivalent to the original one. This shows that your problem is NP-hard.
To show that the 3CNF is complete, we need to show that it is possible to extend any truth assignment of up to three variables to a satisfying assignment, unless this truth assignment falsifies a clause.
Let $\alpha$ be a truth assignment of up to three variables which doesn't falsify any clause. We can complete it to a truth assignment which satisfies the clauses $C'_1,\ldots,C'_m$. It remains to show that we can satisfy each equality gadget.
Out of $w_1^{(i,j,k)},\ldots,w_4^{(i,j,k)}$, at least one is not set by $\alpha$, and we set it to $1$. This allows us to satisfy the first half of the gadget; this requires some case analysis, but the idea is that this half of the gadget expresses
$$
x_i^{(j)} \stackrel {w_1^{(i,j,k)}} \Longrightarrow
z_1^{(i,j,k)} \stackrel {w_2^{(i,j,k)}} \Longrightarrow
z_2^{(i,j,k)} \stackrel {w_3^{(i,j,k)}} \Longrightarrow
z_3^{(i,j,k)} \stackrel {w_4^{(i,j,k)}} \Longrightarrow
x_i^{(k)},
$$
and substituting $w_t^{(i,j,k)} = 1$ breaks the implication cycle.
We can similarly satisfy the second half of the gadget, which expresses
$$
x_i^{(k)} \stackrel {w_5^{(i,j,k)}} \Longrightarrow
z_4^{(i,j,k)} \stackrel {w_6^{(i,j,k)}} \Longrightarrow
z_5^{(i,j,k)} \stackrel {w_7^{(i,j,k)}} \Longrightarrow
z_6^{(i,j,k)} \stackrel {w_8^{(i,j,k)}} \Longrightarrow
x_i^{(j)}.
$$